Proceedings of 1993 IEEE/Tsukuba International Workshop on Advanced Robotics
DOI: 10.1109/icar.1993.337222
|View full text |Cite
|
Sign up to set email alerts
|

The concept of robot society and its utilization

Abstract: Societies are formed as collaborative structures to execute tasks which are not possible or are difficult for individuals alone. There are many type of biological societies, but societies formed by machines or robots are still rare. The concept offers, however, interesting possibilities especially in applications where a long term fully autonomous operation is needed and/or the work to be done can be executed in a parallel way by a group of individuals. The paper introduces the basic control and communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Having the capabilities associated with the latter, social robot will remove a physical obstacle that may be harmful for humans and/or other robots. These functionalities can convert anonymous groups of robots into a society of individualized socialized robots (Halme et al, 1993), (Bugental & Grusec, 2007).…”
Section: Issues Of Socialization Of Ng-cpssmentioning
confidence: 99%
“…Having the capabilities associated with the latter, social robot will remove a physical obstacle that may be harmful for humans and/or other robots. These functionalities can convert anonymous groups of robots into a society of individualized socialized robots (Halme et al, 1993), (Bugental & Grusec, 2007).…”
Section: Issues Of Socialization Of Ng-cpssmentioning
confidence: 99%
“…The connection can for example be built to the information system of the society, rather than to each individual. 405…”
Section: Crowdsourcing and Technology Platforms (Lars Bo Jeppesen)mentioning
confidence: 99%
“…1 If these rules could be found and formulated, then, a real lifelike society of robots with the same kind of astonishing robustness and adaptivity could be constructed. Such system is called robot society, see Halme et al, 2 where a detailed presentation of the concept can be found. Robots in the society might be also called (physical) autonomous agents according to the meaning given to this term usually in the literature.…”
Section: Introductionmentioning
confidence: 99%